(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Michael Morris’ book Every step of the way: The journey to freedom in South Africa is an impressively compiled survey of South African history from the earliest times to the present-day. With a foreword by the then South African Minister of Education Kader Asmal, this book is unabashedly identified as “…part of a larger effort by the Ministry of Education to revitalise the study of history” in the country. The book can therefore be considered as more than just a narrative of the South African story, but also a nation-building project meant to illustrate how South Africa came to be the nation it is today.